Investigation of soot formation in a novel diesel fuel burner - Palazzo, Natascia; Kögl, Matthias; Bauer, Philipp; Mannazhi, Manu Naduvil; Zigan, Lars; Huber, Franz; Will, Stefan (Energies, 2019)
In the present work, a novel burner capable of complete pre-vaporization and stationary combustion of diesel fuel in a laminar diffusion flame has been developed to investigate the effect of the chemical composition of diesel fuel on soot formation. For the characterization of soot formation during diesel combustion we performed a comprehensive morphological characterization of the soot and determined its concentration by coupling elastic light scattering (ELS) and laser-induced incandescence (LII) measurements. With ELS, radii of gyration of aggregates were measured within a point-wise measurement volume, LII was employed in an imaging approach for a 2D-analysis of the soot volume fraction. We carried out LII and ELS measurements at different positions in the flame for two different fuel types, revealing the effects of small modifications of the fuel composition on soot emission during diesel combustion.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Elastic light scattering; Fuel comparison; Laser-induced incandescence; Pre-vaporized diesel combustion